MESHING PERFORMANCE ANALYSIS OF FLEXIBLE GEAR TOOTH PROFILE MODIFICATION OF HARMONIC REDUCER (MT) - XU ShaoYan; LI GuoPing; LUO LiMin; GONG LinHuan; LI Chen; LOU JunQiang (Jixie qiangdu)
To explore the effect of the tooth profile modification of the flexible gear on the meshing performance of the harmonic reducer, an assembly model of the hollow harmonic reducer was established, and the meshing situation of the flexible gear and the rigid gear was analyzed by the finite element method. The equivalent deformation and equivalent stress of the double-arc tooth profile in the no-load and load process are used as the comparison conditions. Comprehensively consider the amount of flexible gear tooth profile tooth tip modification, and adjust the tooth height inclination of the flexible gear tooth profile axis at the same time, and calculate the equivalent deformation stress after the tooth profile modification under the same boundary conditions. The comparison results show that the neutral layer curves of the front and rear edges of the flexible gear tooth are extracted under no-load and load conditions. The equivalent deformation of the flexible gear is basically unchanged, but the maximum equivalent stress is reduced to 80% and 76.6% respectively, and the meshing performance is improved. Related researches provide useful attempts and references for the design, evaluation and transmission performance optimization of harmonic reducers.